Water and Energy Conservation of Rainwater Harvesting System in the Loess Plateau of China - Zhi-yun JIANG; Xiao-yan LI; Yu-jun MA (Journal of Integrative Agriculture, 2013)
Water is the source of all the creatures on the earth and energy is the main factor driving the world. With the increasing population and global change, water and energy conservation have become worldwide focal issues, particularly in the water-stressed and energy-limited regions. Rainwater harvesting, based on the collection and storage of rainfall runoff, has been widely used for domestic use and agricultural production in arid and semiarid regions. It has advantages of simple operation, high adaption, low cost and less energy consumption. This study reviewed rainwater harvesting systems adopted in the Loess Plateau of China and analyzed water use efficiency (WUE) for various rainwater harvesting techniques. Supplemental irrigation using harvested rainwater could increase crop yield by more than 30%, and WUE ranged from 0.7 to 5.7 kg m−3 for spring wheat, corn and flax, and 30-40 kg m−3 for vegetables. Moreover, energy consumption for rainwater harvesting based on single family was compared with traditional water supply in the city of the Loess Plateau using the life cycle assessment (LCA) method. Results showed that energy consumption yielded per unit harvested rainwater was 25.96 MJ m−3 yr−1 which was much less than 62.25 MJ m−3 yr−1 for main water supply in Baoji City, Shanxi Province, meaning that rainwater harvesting saved energy by 139.8% as compared to the main water supply system. This study highlights the importance and potential of rainwater harvesting for water and energy conservation in the near future.